2002
DOI: 10.1002/meet.1450390143
|View full text |Cite
|
Sign up to set email alerts
|

Once found, what then? A study of “keeping” behaviors in the personal use of Web information

Abstract: This observational study investigates the methods people use in their workplace to organize web information for re‐use. In addition to the bookmarking and history list tools provided by web browsers, people observed in our study used a variety of other methods and associated tools. For example, several participants emailed web addresses (URLs) along with comments to themselves and to others. Other methods observed included printing out web pages, saving web pages to the hard drive, pasting the address for a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 21 publications
7
109
0
3
Order By: Relevance
“…Studies conducted as part of the Keeping Found Things Found project [Jones et al 2002[Jones et al , 2003Bruce et al 2004] found that memory problems hindered participants' ability to re-find all of their useful documents. Participants were generally good at getting back to a desired information item (e.g., edocument, email message or web page) if they remembered to look for it.…”
Section: Pim and Memory Problemsmentioning
confidence: 99%
“…Studies conducted as part of the Keeping Found Things Found project [Jones et al 2002[Jones et al , 2003Bruce et al 2004] found that memory problems hindered participants' ability to re-find all of their useful documents. Participants were generally good at getting back to a desired information item (e.g., edocument, email message or web page) if they remembered to look for it.…”
Section: Pim and Memory Problemsmentioning
confidence: 99%
“…Later, Barreau and Nardi [5] suggested that the way information is used on the PC desktop should also be the primary determinant of the way it will be organized, stored and retrieved in the personal workspace. Jones et al [20] investigate the methods people use in their workplace to organize web information for re-use (e.g., send email to self or others, print out the web page, etc.) and Ringel [28] analyzed the way virtual desktops and multi-monitor systems are used.…”
Section: Desktop Usage Analysismentioning
confidence: 99%
“…In terms of managing personal information, many works have focused on single content source, in [7], for example, an observational study about how people organise web information for later reuse has been conducted. People in this study utilised several methods to manage their web content such as: printing web pages, saving them locally or keeping a list of URLs along with the typical bookmarking and history lists web browsers provide.…”
Section: Introductionmentioning
confidence: 99%